Relationship between corporate governance mechanisms, IFRS adoption, and audit quality in Saudi Arabia - Fallatah, Emad Mohammed (2021)
Recent years have seen a paradigm shift in corporate governance mechanisms, adopting IFRS, and audit quality by significant policymakers, professional bodies, and other stakeholders to stimulate substantial economic growth. The shift aims to support the global drivers of economic growth, that is, to promote efficient capital markets, corporate reporting, quality investments, and a favorable business climate. Quality audit practices aim to produce quality financial reports (i.e., the final output), while quality earnings aim to safeguard investors and creditors' investment interests (i.e., returns on investment and collections of obligations) so that they can make better informed economic judgments. Unlike developed countries with better economic stability and rigorous laws and regulatory systems, emerging economies are still striving to achieve that level of stability and the extent of control towards the law (OECD, 2019). In Saudi Arabia, the level of audit quality and governance practices have suffered due to the lack of control and the clarity of regulations, hence the gaps in the adopted reporting standards. This study aims to examine the moderating effect of IFRS adoption on the relationship between corporate governance mechanisms and audit quality among listed non-financial firms in Saudi Arabia. The pre-IFRS adoption period between 2013 and 2015, and the post-IFRS adoption period between 2016 and 2018, for listed non-financial firms, were taken into focus. The sub-components of corporate governance (i.e., interlocking board membership, reputational board capital, board political connection, board gender diversity, and board nationality), audit committee mechanisms (i.e., audit committee independence and audit committee meeting), and ownership structures (i.e., managerial ownership and ownership concentration) were examined for their impact on the audit quality value. The level of discretionary accruals was used as a proxy for audit quality. The dynamic panel estimation of the second step system Generalised Method of Moments (SGMM2) was used for data analysis. The sample in this study consists of 165 Saudi public listed firms. Based on the dynamic panel estimation of the second step system Generalised Method of Moments (SGMM2), findings revealed that the firms' governance mechanisms had a significant positive impact on the discretionary accruals, thereby leading to an alleviated audit quality during the pre-IFRS adoption. During this period, the Saudi Capital Market Authority could not clearly define the different practices of corporate governance mechanisms. This had resulted in a lack of inclusion of the CG Code of Conduct in the Saudi business environment. In contrast, during the post-IFRS adoption period, the relationship between corporate governance mechanisms and audit quality was strengthened by the IFRS adoption, the revised code of governance, and the code of ethics requirements. The empirical findings suggest that corporate governance mechanisms are significant in improving the level of audit quality in Saudi Arabia post-IFRS adoption period rather than the pre IFRS adoption period. The overall results of this study offer valuable feedback to policymakers and other interested parties in Saudi Arabia (and also GCC and Middle Eastern countries that share the same economic, political, social, and cultural environment). Findings can help them better understand the role corporate governance mechanisms play in enforcing, monitoring, and governing audit quality processes and practices. It also facilitates them in evaluating the experience of IFRS adoption towards improving the effectiveness of their corporate mechanisms and the level of audit quality.